Development of PBL Based E-Student Worksheet Using an Ethnoscience Approach to Improve Students' Character Values and Conservation Attitudes on Redox Material - Artika; Jimmi Copriady; Rasmiwetti (Postgraduate, University of Mataram, 2024)
The study aimed to develop a PBL Integrated Ethnoscience-Based e-Student Worksheet focused on redox material, ensuring its validity, and to determine its impact on enhancing students' character values and conservation attitudes. Utilizing the Research and Development (R&D) approach with the Plomp model, the study incorporated various data collection methods such as interviews, student questionnaires, validation sheets, and user response surveys. Validation involved assessments from three material experts and media specialists. Initial trials encompassed one-on-one assessments with students of varying abilities and feedback from teachers and students. The larger-scale trial adopted a pre-experimental Pretest-Posttest Control Group design. The outcomes revealed that the e-Student Worksheet achieved high validation scores from both material and media experts, while feedback from users indicated its effectiveness. Importantly, significant improvements in students' character values and conservation attitudes were observed post-implementation of the e-Student Worksheet, as confirmed by paired t-tests. In summary, the use of the Flip Builder application in crafting the E-Student Worksheet, grounded in PBL and ethnosciences, not only received strong validation but also positively impacted students' character development and conservation perspectives.